Fístulas anales - Jorge Arturo Sánchez S.; Jaime Escobar Triana; Edgar Sastre; Ernesto Urdaneta V. (Revista de la Facultad de Medicina, 1981)
A comprehensive review on the records of anal fistulas in the last ten years at Hospital San Juan de Dios Bogotá is presented; sorne aspects of this entíty are analyzed, as well as the results of their management.